Synbiotic goat milk kefir improves health status in rats fed a high-fat and high-fructose diet - Nurliyani, Nurliyani; Harmayani, Eni; Sunarti, Sunarti (2022)
Background and Aim: Kefir, a natural probiotic containing bacteria and yeast, is a fermented milk product, whereas glucomannan from porang tuber (Amorphophallus oncophyllus) is prebiotic in vivo. Simvastatin is a potent lipid-lowering statin that can be utilized for pharmacological therapy in obesity. This study aimed to determine the effect of goat milk kefir supplemented with porang glucomannan (synbiotic kefir) and goat milk kefir without glucomannan (probiotic kefir) on blood glucose, hemoglobin A1c (HbA1c), free fatty acids (FFAs), tumor necrosis factor-alpha (TNF-α), gene expression of peroxisome proliferator-activated receptor gamma (PPARγ), and insulin-producing cells in rats fed a high-fat and high-fructose (HFHF) diet. Materials and Methods: Male Sprague-Dawley rats were divided into five dietary groups: (1) Normal control, (2) rats fed HFHF, (3) rats fed HFHF+probiotic kefir, (4) rats fed HFHF+synbiotic kefir, and (5) rats fed HFHF+simvastatin. All of these treatments were administered for 4 weeks. Results: There were no significant differences in plasma glucose levels in HFHF diet-fed rats before and after treatment. However, plasma HbA1c and TNF-α decreased, and FFAs were inhibited in rats after treatment with synbiotic kefir. Synbiotic kefir decreased the gene expression of PPARγ2 in HFHF diet-fed rats but did not affect the total number of islets of Langerhans and insulin-producing cells. Conclusion: Synbiotic kefir improved the health of rats fed an HFHF diet by decreasing HbA1c, TNF-α, and PPARγ2 gene expression and preventing an increase in FFAs. Copyright: Nurliyani, et al. Open Access. This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.